Predegenerated great auricular nerve graft in facial nerve defects (2014)
To compare axonal regeneration in an animal model after the repair of facial nerve defects with pre-degenerated (PD) and non-PD (NPD) great auricular nerve grafts. The buccal branch of the facial nerve was completely sectioned in 18 New Zealand rabbits, which were randomized to 3 treatment groups: PD great auricular nerve graft repair (PD group), NPD great auricular nerve graft repair (NPD group), and immediate end-to-end repair (control group). Axonal regeneration was examined using optical microscopy to assess the following variables: total number of myelinated axons and regenerating sprouts (MARS) that crossed the distal anastomosis, numbers of intra and extrafascicular MARS, and area of myelinated axons. The total number of myelinated axons (p = 0.008) and intrafascicular axons (p = 0.02) that crossed the distal anastomosis significantly differed between the NPD and control group. No significant differences were observed between the PD and control group or between the PD and NPD groups. Nerve repair with PD grafts could be an alternative treatment in the management of injuries resulting in facial nerve gaps. Severe traumatic injuries of the facial nerve frequently cause long-term disability secondary to lack of axonal regeneration and poor selectivity of motor endplate reinnervation. Most clinicians consider that primary nerve reconstruction provides the best conditions for axonal regeneration after traumatic nerve interruption (1,2). However, primary reconstruction is only seldom possible because of long gaps between the injured nerve stumps or because of shrinkage of the nerve stumps. In such cases, the gap should be bridged with a length of autologous nerve to restore nerve continuity; however, the success of this surgical procedure can be limited by the barriers formed by the sutures lines, poor revascularization of the nerve graft, or misdirected axonal regeneration (3). There is some documented experimental evidence of enhancement of axonal regeneration within a predegenerated (PD) graft. Predegeneration refers to the process of inducing severe neural tissue damage in the donor nerve in situ for a period prior to harvesting the nerve, to allow Wallerian degeneration to occur in the neural graft. The main objective of the present randomized controlled experimental trial was to determine the histomorphologic patterns of a PD neural graft transplanted into a recreated and very common cranial base surgery scenario, where a proximal denervated polifascicular motor neural stump was available for reconstruction with the interposition graft.